Seizing Opportunity to Improve Family Business on PKK Cadres: Memanfaatkan Peluang untuk Meningkatkan Bisnis Keluarga pada Kader PKK - Rusliati, Ellen; Mulyaningrum, Mulyaningrum; Lisda, Ruslina; Laila Nurwulan, Liza; A. Sufyani, Mujibah (Universitas Lancang Kuning, 2025)
PKK members need to take advantage of their opportunities and potential to run a family business professionally. This community service (PPM) aims to motivate and increase the entrepreneurial spirit of PKK cadres to run a family business so that it can improve welfare. PPM is carried out with technical training in the form of lectures, discussions, practices, and assistance on family business management, which is carried out at the Village Hall and visits to production sites. The training participants consisted of 25 cadres and 10 Dasa Wisma. The implementation time is for 4 (four) months, namely from September to December 2023. The results show an increased understanding of the use of business opportunities, entrepreneurial spirit, and the desire to change to meet the demands of competition. Furthermore, support from the village government, and PKK Administrators. Village-owned enterprises (VOEs), and universities were needed to improve management capabilities, facilitate PIRT and halal certification, as well as assist in managing family businesses. The importance of this PPM is to provide knowledge, motivation, and assistance so that family businesses are guaranteed sustainability.